2017
DOI: 10.17569/tojqi.343218
|View full text |Cite
|
Sign up to set email alerts
|

Education on Programming with Robots: Examining Students’ Experiences and Views

Abstract: The present study aimed to determine the success and views of students receiving education on programming with robots. In the study, which was carried out with the mixed research method, the data were collected via a creative problem-solving test, applied performance evaluation test for programming with robots, a semi-structured interview form. The creative problem-solving skills test was taken from PISA 2012 conducted by OECD. The study was carried out with 9 secondary school students. In the application proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Results indicated that the problem-solving skills of middle school students increased significantly by coding VEX IQ robots. When we look at the results of the studies conducted in the literature, it is seen that both block-based programming environments and robotic activities contribute positively to problem-solving skills (Cankaya, Durak, & Yunkul, 2017;Shin & Park, 2014). However, some studies in the literature show that robotic or block-based programming causes not a significant difference (Cinar, 2019;Kalelioglu, 2015;Kalelioglu & Gulbahar, 2014).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Results indicated that the problem-solving skills of middle school students increased significantly by coding VEX IQ robots. When we look at the results of the studies conducted in the literature, it is seen that both block-based programming environments and robotic activities contribute positively to problem-solving skills (Cankaya, Durak, & Yunkul, 2017;Shin & Park, 2014). However, some studies in the literature show that robotic or block-based programming causes not a significant difference (Cinar, 2019;Kalelioglu, 2015;Kalelioglu & Gulbahar, 2014).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Bu doğrultuda geleceğin öğretmeni olacak adayların programlama ve programlama öğretimine yönelik algı, tutum ve görüşlerini ortaya çıkarmak için yürütülen çalışmaların, ilgili öğretim sürecini daha iyi tasarlayabilmek için önem arz ettiği düşünülmektedir. İlgili alanyazında BT öğretmen adaylarının, bilgisayar programlamaya yönelik öz-yeterlik algıları ve tutumlarına (Yükseltürk & Altiok, 2017), programlamaya yönelik tutumlarına (Özyurt & Özyurt, 2015;Chen, Haduong, Brennan, Sonnert & Sadler, 2019), bilgisayar programlama öğretimine yönelik görüşlerine (Yükseltürk & Altiok, 2015;Çankaya, Durak & Yünkül, 2017) ve bu süreçte kullanılan araçlara ilişkin algılarına (Yükseltürk & Altiok, 2016;Davenport, 2018) yönelik çalışmaların mevcut olduğu görülmektedir. Ayrıca, programlama sürecini etkileyen öz-yeterlik gibi diğer faktörlerinde dikkate alınması gerekli görülmektedir (Ramalingam, LaBelle & Wiedenbeck, 2004;Jegede, 2009).…”
Section: öZ-yeterlik Algısıunclassified
“…As shown by Magnenat et al robots can be used in this field with great effect to teach the otherwise often abstract concept of event handling [15]. The effect of robots as a general tool to teach programming is also commonly tested and while the results are mixed [16,17] the robots were able to increase the motivation of the students [18].…”
Section: Related Workmentioning
confidence: 99%